2009
DOI: 10.1111/j.1468-2982.2009.01864.x
|View full text |Cite
|
Sign up to set email alerts
|

Sumatriptan alleviates nitroglycerin-induced mechanical and thermal allodynia in mice

Abstract: The association between the clinical use of nitroglycerin (NTG) and headache has led to the examination of NTG as a model trigger for migraine and related headache disorders, both in humans and laboratory animals. In this study in mice, we hypothesized that NTG could trigger behavioural and physiological responses that resemble a common manifestation of migraine in humans. We report that animals exhibit a dose-dependent and prolonged NTG-induced thermal and mechanical allodynia, starting 30–60 min after intrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
282
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(307 citation statements)
references
References 48 publications
(53 reference statements)
22
282
3
Order By: Relevance
“…Bates et al showed the mechanical allodynia and heat hyperalgesia developed in the hind paw after injection of NTG, which was similar to results in the present study. 3) On the other hand, Galeotti and Ghelardini reported that NO donors NTG and sodium nitroprusside induced cold allodynia and heat hyperalgesia in the hind paw. 6) The induction of hind paw cold allodynia was different from our study, but it seems to be associated with the difference of mice strain or experimental protocol (C57BL/6 male mice vs. Swiss albino male mice, and acetone solution test vs. cold plate test).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bates et al showed the mechanical allodynia and heat hyperalgesia developed in the hind paw after injection of NTG, which was similar to results in the present study. 3) On the other hand, Galeotti and Ghelardini reported that NO donors NTG and sodium nitroprusside induced cold allodynia and heat hyperalgesia in the hind paw. 6) The induction of hind paw cold allodynia was different from our study, but it seems to be associated with the difference of mice strain or experimental protocol (C57BL/6 male mice vs. Swiss albino male mice, and acetone solution test vs. cold plate test).…”
Section: Discussionmentioning
confidence: 99%
“…5) In mice, a single injection of NTG induces acute mechanical, cold, and thermal hypersensitivity, which persists up to four hours post-injection. 3,6) Recently Pradhan et al reported that repetitive injections of NTG induced chronic mechanical hypersensitivity, mimicking the chronic migraines observed in human patients. 7) Since mechanical and thermal hyperalgesia are indicators of migraine-related sensory abnormalities, 7,8) a rodent model of NTG-evoked hypersensitivity is useful for investigating the mechanisms involved in the development of these abnormalities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A dose-dependent and prolonged NTG-induced thermal and mechanical allodynia was detected in mice, which were alleviated by sumatriptan (Bates et al, 2010). NTG caused a hyperalgesic response in the tail-flick test, which was attenuated by pre-or co-treatment with non-peptide CGRP receptor antagonist MK-8825 (Greco et al, 2013), inhibition of which receptor is effective in migraine too (Olesen et al, 2004).…”
Section: Nitroglycerin Model Of Migraine Headachementioning
confidence: 90%
“…c-fos, CGRP [98,136], nNOS-immunoreactivity in the NTG model [89], and c-fos [137], nNOS [111], CGRP alterations [110] following the ES of the TRG.…”
Section: Electrical Stimulation Of the Tsmentioning
confidence: 99%